1999
DOI: 10.1681/asn.v1081689
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Glomerular Heparan Sulfate Correlates with Complement Deposition and Albuminuria in Active Heymann Nephritis

Abstract: Abstract. In a time-study of active Heymann nephritis, the expression of agrin, the main heparan sulfate proteoglycan in the glomerular basement membrane, was analyzed in relation to deposition of IgG and complement in the glomerular capillary wall and the development of albuminuria. Binding of IgG autoantibodies to the glomerular capillary wall could be detected from 2 wk onward, followed by activation of complement after 6 wk. Progressive albuminuria developed from 6 wk onward to a level of 274 ± 68 mg/18 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…187 In MN, alternative pathway activation may also occur independently of immune complexes, due to local complement dysregulation. In particular, the loss of heparan sulfate chains from the glomerular basal membrane, which has been observed in human and experimental MN, 183,188,189 could lead to impaired recruitment of factor H, the major inhibitor of the AP in plasma. It has also been posited that FHAA, which have been reported in a small subset of patients with primary MN, 190,191 may contribute to the activation of the AP.…”
Section: Membranous Nephropathymentioning
confidence: 99%
“…187 In MN, alternative pathway activation may also occur independently of immune complexes, due to local complement dysregulation. In particular, the loss of heparan sulfate chains from the glomerular basal membrane, which has been observed in human and experimental MN, 183,188,189 could lead to impaired recruitment of factor H, the major inhibitor of the AP in plasma. It has also been posited that FHAA, which have been reported in a small subset of patients with primary MN, 190,191 may contribute to the activation of the AP.…”
Section: Membranous Nephropathymentioning
confidence: 99%
“…Heparan sulphate chains in the glomerular basement membrane normally recruit plasma factor H to regulate the local alternative pathway of complement. Expression of heparanases leading to loss of glomerular heparan sulphate has been associated with complement deposition and proteinuria in Heymann nephritis ( 72 ). Several reports further suggested that anti-complement factor H (anti-CFH) antibodies may be expressed in MN, although the evidence is conflicting.…”
Section: Evidence Of Complement Pathway Activation In Membranous Neph...mentioning
confidence: 99%